Pengaruh Islamic Intellectual Capital dan Zakat Funds terhadap Nilai Perusahaan Bank Syariah di Indonesia - Defriko Gusma Putra; Syailendra Eka Saputra; Irma Suryani Indra (Universitas Negeri Padang, 2025)
This research objectives to examine the influence of Islamic intellectual capital and zakat funds on the firm value of Islamic banks in Indonesia. Using a quantitative approach with panel data of 16 Islamic banks listed on the Indonesia Stock Exchange during the 2020–2024 period (80 observations), the analysis was conducted through panel data regression with model selection using the Chow and Hausman tests. The results showed that the best model was the Fixed Effect Model. Empirical findings reveal that Islamic intellectual capital has a positive and significant effect on firm value, in line with the Resource-Based View perspective which emphasizes the importance of human capital, structural capital, and relational capital in creating competitive advantage. Zakat funds are also proven to have a significant positive effect on firm value, supporting the principle of Sharia Enterprise Theory that zakat accountability reflects the fulfillment of the principles of welfare, death, and benefit (maslahah) which are the basis for the operations of Islamic financial institutions. Simultaneously, both variables contribute 54.10% to the variation in firm value. These findings confirm that strengthening Sharia-based intellectual capacity and transparent zakat management play a role in increasing firm value and the competitiveness of Islamic banks. This research provides an important influence for Islamic bank management and regulators in developing policies to increase the value and sustainability of Islamic financial institutions.